2023
DOI: 10.3389/fphar.2023.1243934
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the involvement of long non-coding RNAs in doxorubicin resistance of cancer

Hai-Bo Zhang,
Yang Hu,
Jun-Li Deng
et al.

Abstract: Doxorubicin is one of the most classical chemotherapeutic drugs for the treatment of cancer. However, resistance to the cytotoxic effects of doxorubicin in tumor cells remains a major obstacle. Aberrant expression of long non-coding RNAs (lncRNAs) has been associated with tumorigenesis and development via regulation of chromatin remodeling, transcription, and post-transcriptional processing. Emerging studies have also revealed that dysregulation of lncRNAs mediates the development of drug resistance through mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 144 publications
(163 reference statements)
0
2
0
Order By: Relevance
“…LINC02562 (long intergenic non-protein coding RNA 2562) is part of a class of RNAs that, while not coding for proteins, can also affect gene regulation. Long non-coding RNAs are known to be involved in a variety of biological processes, including chromatin remodeling, transcriptional control and post-transcriptional modifications (33,34). Similarly, the small nuclear RNA U4atac Pseudogene 9 (RNU4ATAC9P) may be involved in minor spliceosome function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LINC02562 (long intergenic non-protein coding RNA 2562) is part of a class of RNAs that, while not coding for proteins, can also affect gene regulation. Long non-coding RNAs are known to be involved in a variety of biological processes, including chromatin remodeling, transcriptional control and post-transcriptional modifications (33,34). Similarly, the small nuclear RNA U4atac Pseudogene 9 (RNU4ATAC9P) may be involved in minor spliceosome function.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the small nuclear RNA U4atac Pseudogene 9 (RNU4ATAC9P) may be involved in minor spliceosome function. Traditionally thought to be non-functional, recent studies have suggested that pseudogenes, and types of pseudogenes like retrotransposons, may play a regulatory role in gene expression (34,35). The similarity of the CABS1 UGR to these other UGRs could provide clues to how CABS1 is regulated in the body and perhaps some of its functions.…”
Section: Discussionmentioning
confidence: 99%